Chronic ecotoxic effects to Pseudomonas putida and Vibrio fischeri, and cytostatic and genotoxic effects to the hepatoma cell line (HepG2) of ofloxacin photo(cata)lytically treated solutions - Vasquez Christodoulou, Marlen; Garcia-Käufer, Manuel; Hapeshi, Evroula; Menz, Jakob; Kostarelos, Konstantinos; Fatta-Kassinos, Despo; Kümmerer, Klaus (My University, 2013)
Ofloxacin (OFL), a broad-spectrum and widespread-used photolabile fluoroquinolone, is frequently found in treated wastewaters, aquatic and terrestrial ecosystems leading to increasing concern during the past decades regarding its effects to the environment and human health. The elimination of OFL and other xenobiotics by the application of advanced oxidation processes using photolytic (PL) and photocatalytic (PC) treatments seems promising. However, an integrated assessment scheme is needed, in which, not only the removal of the parent compound, but also the effects of the photo-transformation products (PTPs) are investigated. For this purpose, in the present study, a chronic ecotoxic assessment using representative bacteria of marine and terrestrial ecosystems and a cytostatic and genotoxic evaluation using hepatoma cell line were performed. PL and PC treatments of OFL were applied using UV radiation. The photo-transformation of OFL during the treatments was monitored by DOC measurements and UPLC-MS/MS analysis. The chronic ecotoxicity of OFL and treated samples was evaluated using Pseudomonas putida and Vibrio fischeri; whereas the cytostasis and genotoxicity were estimated by the cytokinesis-block micronucleus assay (CBMN). The main results suggest that photo-transformation of OFL took place during these treatments since the concentration of OFL decreased when the irradiation time increased, as quantified by UPLC-MS/MS analysis, and this was not coupled with an analogous DOC removal. Furthermore, nine compounds were identified as probable PTPs formed through piperazinyl dealkylation and decarboxylation. The ecotoxicity of treated solutions to the bacteria studied decreased while the cytostasis to the hepatoma cell line remained at low levels during both treatments. However, the genotoxicity to the hepatoma cell line demonstrated a different pattern in which treated samples induced a greater number of MNi for the 4-16 min of irradiation (p<0.05) during both treatments. After 64 min of irradiation, the effects decreased to non genotoxic levels (p<0.05). These findings suggest that UV radiation for various treatment processes (catalytic or not), such as disinfection, may create genotoxic by-products. Therefore, in relevant technical applications, the residence time during treatment should receive special attention.
Keywords: Ofloxacin; Phototransformation product; Photolysis; Photocatalysis; Ecotoxicity; Genotoxicity